Non-viral Gene Delivery of Interleukin-1 Receptor Antagonist Using Collagen-Hydroxyapatite Scaffold Protects Rat BM-MSCs From IL-1β-Mediated Inhibition of Osteogenesis - Lackington, William A.; Gomez-Sierra, Maria Antonia; González-Vázquez, Arlyng; O’Brien, Fergal J.; Stoddart, Martin J.; Thompson, Keith (Frontiers in Bioengineering and Biotechnology, 2020)
Although most bone fractures typically heal without complications, a small proportion of patients (≤ 10%) experience delayed healing or potential progression to non-union. Interleukin-1 (IL-1β) plays a crucial role in fracture healing as an early driver of inflammation. However, the effects of IL-1β can impede the healing process if they persist long after the establishment of a fracture haematoma, making it a promising target for novel therapies. Accordingly, the overall objective of this study was to develop a novel gene-based therapy that mitigates the negative effects of IL-1β-driven inflammation while providing a structural template for new bone formation. A collagen-hydroxyapatite scaffold (CHA) was used as a platform for the delivery of nanoparticles composed of pDNA, encoding for IL-1 receptor antagonist (IL-1Ra), complexed to the robust non-viral gene delivery vector, polyethyleneimine (PEI). Utilizing pDNA encoding for Gaussia luciferase and GFP as reporter genes, we found that PEI-pDNA nanoparticles induced a transient gene expression profile in rat bone marrow-derived mesenchymal stromal cells (BM-MSCs), with a transfection efficiency of 14.8±1.8% in 2D. BM-MSC viability was significantly affected by PEI-pDNA nanoparticles as evaluated using CellTiter Blue; however, after 10 days in culture this effect was negligible. Transfection with PEI-pIL-1Ra nanoparticles led to functional IL-1Ra production, capable of antagonizing IL-1β-induced expression of secreted embryonic alkaline phosphatase from HEK-Blue™-IL-1β reporter cells. Sustained treatment with IL-1β (0.1, 1 and 10 ng/ml) had a dose-dependent negative effect on BM-MSC osteogenesis, both in terms of gene expression (Alpl and Ibsp) and calcium deposition. BM-MSCs transfected with PEI-IL-1Ra nanoparticles were found to be capable of overcoming the inhibitory effects of sustained IL-1β (1 ng/ml) treatments on in vitro osteogenesis. Ultimately, IL-1Ra gene-activated CHA scaffolds supported mineralization of BM-MSCs under chronic inflammatory conditions in vitro, demonstrating potential for future therapeutic applications in vivo.